The HEALing (Helping to End Addiction Long-term SM) Communities Study: Protocol for a cluster randomized trial at the community level to reduce opioid overdose deaths through implementation of an integrated set of evidence-based practices. (1st December 2020) - ,; Walsh, Sharon L.; El-Bassel, Nabila; Jackson, Rebecca D.; Samet, Jeffrey H.; Aggarwal, Maneesha; Aldridge, Arnie P.; Baker, Trevor; Barbosa, Carolina; Barocas, Joshua A.; Battaglia, Tracy A.; Beers, Donna; et al.
Highlights: HEALing Communities Study is a parallel-group cluster randomized controlled trial. Communities That Heal intervention's goal is to reduce opioid overdose deaths. Structured consensus decision-making strategy guided study measure development. More than 80 study measure specifications and a common data model were developed. The study will provide methodology and longitudinal community data for research. Abstract: Background: Opioid overdose deaths remain high in the U.S. Despite having effective interventions to prevent overdose deaths, there are numerous barriers that impede their adoption. The primary aim of the HEALing Communities Study (HCS) is to determine the impact of an intervention consisting of community-engaged, data-driven selection, and implementation of an integrated set of evidence-based practices (EBPs) on reducing opioid overdose deaths. Methods: The HCS is a four year multi-site, parallel-group, cluster randomized wait-list controlled trial. Communities (n = 67) in Kentucky, Massachusetts, New York and Ohio are randomized to active intervention (Wave 1), which starts the intervention in Year 1 or the wait-list control (Wave 2), which starts the intervention in Year 3. The HCS will test a conceptually driven framework to assist communities in selecting and adopting EBPs with three components: 1) a community engagement strategy with local coalitions to guide and implement the intervention; 2) a compendium of EBPs coupled with technical assistance; and 3) a series of communication campaigns to increase awareness and demand for EBPs and reduce stigma. An implementation science framework guides the intervention and allows for examination of the multilevel contexts that promote or impede adoption and expansion of EBPs. The primary outcome, number of opioid overdose deaths, will be compared between Wave 1 and Wave 2 communities during Year 2 of the intervention for Wave 1. Numerous secondary outcomes will be examined. Discussion: The HCS is the largest community-based implementation study in the field of addiction with an ambitious goal of significantly reducing fatal opioid overdoses.